Recherches sur les œuvres littéraires du pape Gélase II - Dolbeau, François (Analecta Bollandiana, 1989)
Before becoming chancellor of the Roman Church in 1089, & pope in 1118, Gelasius II (John of Gaeta) spent some fifteen years in the monastery of Monte-Cassino. According to Peter Diaconus he composed while there several hagiographical texts that earned him the reputation of a man of letters. Three of his works were already identified (BHL 2584, 2761 g, 4055 f). A fourth appears here for the first time, a Life of Gregory of Nazianzus (BHL 3668 d) transmitted by a legendary & a breviary from Benevento (Bibl. Cap. 17 and 22, Xllth c.). A prologue, now lost, but known from the summary made by a scholar in 1534, explicitly named John of Gaeta as author. Numerous parallels with the known works of the young hagiographer further confirm the attribution.